The swamplands [videorecording] - Patolot, Miguel Z.; Santos, Gil A. ([S.l.] Makati The Philippine Futuristics Society, [production company] Felta Book Sales [distributor]., 1990)
Shows the importance of wetlands and mangroves to man and marine resources.
Narrator, Bong Lapira; Film editor, Elsa Abellana.
Keywords: Mangrove -- Philippines; Mangrove swamps -- Philippines; Agriculture; Ecology